Root endodermal barrier system contributes to defence against plant‐parasitic cyst and root‐knot nematodes. (3rd September 2019) - Holbein, Julia; Franke, Rochus B.; Marhavý, Peter; Fujita, Satoshi; Górecka, Mirosława; Sobczak, Mirosław; Geldner, Niko; Schreiber, Lukas; Grundler, Florian M. W.; Siddique, Shahid
Significance Statement: Root apoplastic barrier system contributes to the defence against plant‐parasitic nematodes. Summary: Plant‐parasitic nematodes (PPNs) cause tremendous yield losses worldwide in almost all economically important crops. The agriculturally most important PPNs belong to a small group of root‐infecting sedentary endoparasites that includes cyst and root‐knot nematodes. Both cyst and root‐knot nematodes induce specialized long‐term feeding structures in root vasculature from which they obtain their nutrients. A specialized cell layer in roots called the endodermis, which has cell walls reinforced with suberin deposits and a lignin‐based Casparian strip (CS), protects the vascular cylinder against abiotic and biotic threats. To date, the role of the endodermis, and especially of suberin and the CS, during plant–nematode interactions was largely unknown. Here, we analyzed the role of suberin and CS during interaction between Arabidopsis plants and two sedentary root‐parasitic nematode species, the cyst nematode Heterodera schachtii and the root‐knot nematode Meloidogyne incognita . We found that nematode infection damages the endodermis leading to the activation of suberin biosynthesis genes at nematode infection sites. Although feeding sites induced by both cyst and root‐knot nematodes are surrounded by endodermis during early stages of infection, the endodermis is degraded during later stages of feeding site development, indicating periderm formation or ectopic suberization of adjacent tissue. Chemical suberin analysis showed a characteristic suberin composition resembling peridermal suberin in nematode‐infected tissue. Notably, infection assays using Arabidopsis lines with CS defects and impaired compensatory suberization, revealed that the CS and suberization impact nematode infectivity and feeding site size. Taken together, our work establishes the role of the endodermal barrier system in defence against a soil‐borne pathogen.